Serum Lipid Profile and Organ Histology of Albino Rats Fed on Conophor (Tetracarpidium conophorum) Nut Oil-Based Diets (IPS Journal of Nutrition and Food Science, 2023)
The effect of feeding Albino rats with diets composed of oils extracted from raw and processed conophor nuts on the blood serum lipid profile and organ histology were evaluated in this study. Freshly harvested conophor nuts were processed by cooking (at 100 oC for 90 minutes) and toasting (at 145 oC for 50 minutes). Oils extracted from the raw and processed nuts and commercially available soybean oil were fed to four groups of albino rats (each group consisted of five rats) over an experimental period of twenty-eight days after acclimatization. The serum lipid profile [Total cholesterol (TC), α-Lipoprotein (HDL-C), β-Lipoprotein (LDL-C) and Triglycerides (TG)] of the blood obtained from the animals upon sacrifice was determined. Organs (heart and liver) excised from the animals were subjected to histological assay. The serum lipid profile results showed that the parameters were within safe limits. Photomicrographs obtained from the histopathological assay showed that organs from the animals fed on oil from cooked conophor maintained normal histology. Oil from cooked conophor samples gave the best biochemical results compared to oils from both raw and toasted nuts with respect to the effects of consumption on the serum lipid biomarkers and organ histology.
Keywords: conophornut oil; albino rats; serum lipid profile; organ histology